(untitled) (Research, Society and Development, 2024)
Introduction: The initial management of chest pain is a challenging situation for emergency physicians due to the different etiologies. To ensure this effective management, different evaluation protocols were developed. Objective: To identify the clinical evaluation protocols for non-invasive chemotherapy of chest pain in adults in the emergency department (ED). Methods: The study was conducted in accordance with PRISMA and registered on the PROSPERO platform (CRD42024519268). A comprehensive systematic search of international databases, including PubMed and SciELO, was conducted to find articles published up to April 2024. All relevant articles that reported clinical evaluation protocols for chest pain in adults were included in the analysis. Results: This review included articles with guidelines and protocols for the management of chest pain in EDs. We identified that the evaluation of chest pain in ED involves a systematic approach. This analysis includes patient history, physical examination, differential diagnosis, diagnostic tests, and risk stratification. The studies also point to the importance of the 12-lead electrocardiogram, elevations in troponin levels, and the ADP, EDACS, and HEART protocols to determine a patient’s risk of having a major adverse cardiac event. Conclusion: This paper highlights the importance of using evidence-based protocols and decision pathways in the evaluation of chest pain in the ED. It also emphasizes the role of high-sensitivity troponin assays and imaging modalities in the rapid and accurate diagnosis of conditions like acute coronary syndrome.